2016
DOI: 10.1126/sciadv.1601838
|View full text |Cite
|
Sign up to set email alerts
|

General and programmable synthesis of hybrid liposome/metal nanoparticles

Abstract: Programmable liposomes are designed to selectively produce various liposome-nanoparticle hybrids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 50 publications
1
58
0
Order By: Relevance
“…Unilamellar liposomes were purified by centrifugation and washed three times with deionized water to remove residues. Finally, the liposomes encoded with ascorbic acid and CoQ10 were re-suspended using a gold precursor aqueous solution (HAuCl 4 •3H 2 O, tetrachloroauric acid trihydrate, 200 μM) and kept overnight in an agitating incubator at room temperature [24]. The LGNP-CoQ10 structure is shown in Figure 1A.…”
Section: Formation Of Lgnp-coq10mentioning
confidence: 99%
“…Unilamellar liposomes were purified by centrifugation and washed three times with deionized water to remove residues. Finally, the liposomes encoded with ascorbic acid and CoQ10 were re-suspended using a gold precursor aqueous solution (HAuCl 4 •3H 2 O, tetrachloroauric acid trihydrate, 200 μM) and kept overnight in an agitating incubator at room temperature [24]. The LGNP-CoQ10 structure is shown in Figure 1A.…”
Section: Formation Of Lgnp-coq10mentioning
confidence: 99%
“…Nowadays, to overcome these limitations, hybrid systems have begun to attract attention. The use of vesicles in such systems has improved their colloidal stability and intracellular delivery efficiency . Nanoparticles in vesicular hybrid systems should be embedded within the bilayer.…”
Section: Hybrid Vesicular Delivery Systemsmentioning
confidence: 99%
“…These liposomes can produce stronger photoacoustic signals (1.5-fold) in the NIR region than blood. Furthermore, when there were drugs (i.e., doxorubicin (Dox)) within these liposomes, the irradiation with the NIR pulse laser would disrupt the liposomes and trigger the 100% release of these pre-encapsulated drugs within 10 s. Recently, Lee et al [ 20 ] further demonstrated that the reducing agent could be re-encoded before the metal precursors diffused across lipid bilayers self-crystallized to metal nanoparticles in the liposomes.…”
Section: Synthesis Of Gold Nanoparticle-liposomesmentioning
confidence: 99%